The Health System Costs of Potentially Inappropriate Prescribing in Ontario: A Population-based Study - Black, Cody (Université d'Ottawa / University of Ottawa, 2018)
Potentially Inappropriate Prescribing (PIP) is common in Canada yet little is known about its health system costs or which PIPs have the greatest cost impact. This thesis examined the health system costs from hospitalizations, emergency department (ED) visits and medications from all PIP, and for distinct PIP. PIPs were identified in a cohort of older adults in Ontario using a subset of the STOPP/START criteria applicable to health administrative databases, and all analyses were conducted by comparing participants with and without PIP. In study one, the costs from hospitalization, ED visits and newly prescribed medications were identified using population attributable fractions. PIP was identified as responsible for a sizeable portion of all three cost categories, with hospitalization and ED visits costs most highly impacted. Study two compared the incremental costs due to PIP among four distinct PIP criteria selected based on differing frequency and crude costs to validate the use of such characteristics for priority-setting. The crude healthcare costs, as well as the cost of the drug causing the PIP and the frequency of the PIP were identified as likely key characteristics of high-impact PIP. Combined, these studies provide evidence on the overall burden of PIP, while also identifying likely characteristics of high-impact PIP. They suggest interventions at the health system level may be needed to address medication appropriateness and provide information which may be helpful to decision-makers when identifying which PIPs should be targeted for intervention, given no health system level interventions for PIP are currently in place.
Keywords: potentially inappropriate prescribing; health system costs; health administrative databases